1995
DOI: 10.1126/science.7624779
|View full text |Cite
|
Sign up to set email alerts
|

Induction of MHC Class I Genes in Neurons

Abstract: Whether neurons express major histocompatibility complex (MHC) class I genes has not been firmly established. The techniques of confocal laser microscopy, patch clamp electrophysiology, and reverse transcriptase-polymerase chain reaction were combined here to directly examine the inducibility of MHC class I genes in individual cultured rat hippocampal neurons. Transcription of MHC class I genes was very rare in neurons with spontaneous action potentials. In electrically silent neurons, transcription was noted,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
252
0
6

Year Published

1997
1997
2007
2007

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 414 publications
(278 citation statements)
references
References 9 publications
16
252
0
6
Order By: Relevance
“…It has been hypothesized that there is a suppressed inducibility of MHC in functionally active neurons but with eg, viral damage, loss of bioelectric activity of cells could up-regulate MHC molecules for recognition by T cells and thus clearance of abnormal cells. 38 Whether differentiation of muscle fibers, with the expression of MHC on the fiber membrane, contributes to activation or to development of anergy in T lymphocytes is probably dependent on presence of classical co-stimulatory molecules. Such molecules are those within the B7 family, and these have not been demonstrated on muscle fibers to date.…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that there is a suppressed inducibility of MHC in functionally active neurons but with eg, viral damage, loss of bioelectric activity of cells could up-regulate MHC molecules for recognition by T cells and thus clearance of abnormal cells. 38 Whether differentiation of muscle fibers, with the expression of MHC on the fiber membrane, contributes to activation or to development of anergy in T lymphocytes is probably dependent on presence of classical co-stimulatory molecules. Such molecules are those within the B7 family, and these have not been demonstrated on muscle fibers to date.…”
Section: Discussionmentioning
confidence: 99%
“…Hippocampal neurons were prepared from embryonic day 18 Wistar rats as described 17 and cultured in DMEM/10% FCS for 24 h. The medium was then replaced with DMEM/B27 supplement (Invitrogen). For the generation of PC12 cells stably expressing DISC1, FLAG-tagged human DISC1 cDNA in pcDNA3.1( þ ) was linearized by ScaI and transfected to PC12 cells.…”
Section: Plasmidsmentioning
confidence: 99%
“…Oligodendrocytes express MHC class I, and its expression is increased in MS (Hoftberger et al, 2004); therefore, myelin-derived self epitopes on the surface of oligodendrocytes constitute one possible target for CD8 + T cells within the CNS, and studies have reported that myelin-specific CD8 + T cells can trigger the death of cultured human oligodendrocytes (Ruijs et al, 1993;Jurewicz et al, 1998). At first blush, neurons appear less likely targets for direct CD8 + T cell effects, because they express very low levels of MHC class I, and of other components of the class I antigen presentation pathway (Joly et al, 1991;Joly and Oldstone, 1992); however, MHC class I is up-regulated by neurons in response to injury or inflammation (Neumann et al, 1995;Neumann et al, 1997), potentially rendering them vulnerable to CD8 + T cell-mediated cytotoxicity. Indeed, blood-donor derived CD8 + cells can cause axon transection in cultured neurons (Medana et al, 2001).…”
Section: Introductionmentioning
confidence: 99%